COMPARISON STUDY OF TYPE 2 DIABETES MELLITUS INCIDENT IN URBAN AREAS AND RURAL AREAS IN BANTEN - Syam, Asma juita (An Idea Health Journal, 2022)
Diabetes mellitus is recognized as a public health problem in developing countries. Morbidity and mortality rates of Diabetes cases continue to increase in Urban and Rural areas. Therefore, this study aimed to compare the magnitude and risk factors associated with diabetes mellitus in the Urban and Rural areas in Banten. This type of research is observational analytic study using cross sectional design of the 198 respondents consisted of 94 respondents in Urban area and 104 respondents in Rural area. Bivariate analysis with the Independent T Test. Research results indicate that there are differences in risk factors of physical activity (p = 0.00 The T test = -4.65 95% CI; -0.37- -0.15), diabetes status mellitus (p = 0:01 T test = 2.58 CI 95% 5.95 - 44.1) with the incidence of type 2 diabetes mellitus in the Urban and Rural areas whereas family history (p = 0.61 T test = 0.49 The CI 95%; - 0:10 to 0:17), there is no difference in the incidence DMT2 Urban and Rural areas. The prevalence of diabetes mellitus is higher in Urban areas compared to Rural areas. This study suggested that action should be screened for early detection of risk factors, diagnosis and treatment enforcement to reduce complications associated especially in Rural areas.